Novel Algorithm for Improving Tracking Accuracy of Open-Loop Mobile Sun-Tracking System via Different Timing Control Scheme - An-Chow Lai; Ming-Cheng Ho; Kok-Keong Chong; Ming-Hui Tan; Boon-Han Lim; Tonni Agustiono Kurniawan (International Journal of Photoenergy)
This paper proposes a mobile sun-tracking (MST) system to track the sun on the moving vehicle. We have developed a novel MST algorithm using general sun-tracking formulas associated with simple-moving average linear regression (SMALR) to smoothen sun-tracking activity. Furthermore, two different timing control schemes to activate sun tracking are investigated: time lapse (TL) mode and azimuth actuation (AA) mode. For experimental validation, a prototype of MST has been constructed on a small truck moving at constant speed of 30 km/h for field measurements. For the result, AA mode has average pointing error of 110 mrad for the open-loop tracking design (13% better than that of TL mode), which is still far below the half acceptance angle of compound parabolic concentrator at 659 mrad. Since there is no feedback sensor to be implemented in this prototype, optical encoders and CCD camera can be employed in the future work to further reduce the pointing error of MST system.